Improved preparation method and application of porous carbon electrode
By electroless plating and sulfide treatment on porous carbon electrodes, transition metals or transition metal sulfides are uniformly loaded, which solves the problem of insufficient reaction rate of active materials and catalyst preparation problems in flow batteries, and improves the power density and catalytic efficiency of flow batteries.
Patent Information
- Application Number
- CN202411689209.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-01-21
AI Technical Summary
Under the demand for large currents, the electrode reaction rate of active substances on ordinary electrodes cannot be met, resulting in limited charge and discharge current density and power density, and the preparation difficulty and uniformity of the catalyst are difficult to ensure, which hinders the liquid flow. Further development of batteries.
The transition metal element is plated by electroless plating on the porous carbon electrode, and optionally sulfurized to evenly load the transition metal or transition metal sulfide, thereby improving the catalyst adhesion area and efficiency.
The catalyst is uniformly supported on the surface of the porous carbon electrode, which improves the dynamic performance of the active material and battery power density of the flow battery, and provides a new method for the preparation of large-scale flow battery electrode catalysts.
Smart Images

Figure CN119340438A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of liquid flow batteries, and specifically to an improved preparation method and application of a porous carbon electrode. Background Art
[0002] In recent years, the storage and reuse of renewable energy has become a key part of efforts to build a clean, low-carbon, safe and efficient energy system. Under this premise, low-cost and long-life energy storage of renewable energy is a prerequisite for its incorporation into the traditional power grid system. Compared with lithium-ion batteries with high energy storage costs and limited power and energy decoupling capabilities, redox flow battery technology is one of the most promising alternatives for existing grid-scale energy storage. It has high scalability and the characteristics of energy and power decoupling control, so it can be better applied to the storage and reuse of wind power, solar energy and other renewable energy sources with large fluctuations and discontinuities.
[0003] Liquid flow batteries are mainly composed of four modules: electrodes, ion exchange membranes, liquid storage tanks with electrolytes, and pumps. The electrodes themselves do not undergo redox reactions, but only provide a reaction site for active substances in the solution. Liquid flow batteries are different from secondary batteries such as lithium-ion batteries in that the electroactive substances and electrodes in liquid flow batteries are completely separated, achieving independent design of battery power and capacity, so that they can be adapted to various energy storage fields.
[0004] However, in the electrolyte system of polysulfide flow batteries and iron-chromium flow batteries, since the electrode reaction rate of active substances on ordinary electrodes cannot meet the needs of large currents, it is often necessary to develop high-efficiency catalysts to improve the kinetics of active substances to increase the charge and discharge current density, thereby further improving the power density of flow batteries. However, in the large-scale application of flow batteries, the difficulty in preparing a large number of catalysts and the difficulty in ensuring uniformity have hindered the further development of flow batteries. Summary of the invention
[0005] In view of the shortcomings of the prior art, the purpose of this application is to provide an improved preparation method of a porous carbon electrode to solve the problems raised in the above background technology.
[0006] According to one aspect of the present application, an improved method for preparing a porous carbon electrode is provided, characterized in that the method comprises:
[0007] Chemical plating is performed on the porous carbon electrode to plate the transition metal element on the porous carbon electrode to obtain an improved porous carbon electrode;
[0008] The improved preparation method also includes the step of subjecting the transition metal element plated on the porous carbon electrode to a sulfurization treatment.
[0009] Preferably, the porous carbon electrode comprises one of carbon felt, graphite felt and carbon paper.
[0010] Preferably, the transition metal element includes at least one of Ni, Cu, Ag, Au, Zn, Cr and Co.
[0011] Preferably, the plating solution temperature of the chemical plating is 20-95° C., and the chemical plating time is 5-30 min.
[0012] Preferably, the sulfiding liquid used in the sulfidation treatment is a polysulfide solution or a thioacetamide solution.
[0013] Preferably, the sulfiding liquid is a Na 2S 2 solution or a thioacetamide aqueous solution.
[0014] Preferably, the concentration of the Na 2S 2 solution is 0.5 to 6 mol / L, and the concentration of the thioacetamide aqueous solution is 0.01 to 0.1 g / mL.
[0015] Preferably, the reaction temperature of the sulfurization treatment is 80-200° C., and the reaction time of the sulfurization reaction is 2-10 hours.
[0016] Preferably, before the chemical plating, the method further comprises the steps of pre-treating and activating the porous carbon electrode in sequence;
[0017] The pretreatment step includes: placing the porous carbon electrode in a mixed acid solution and heating it at 60-100° C. for 1-10 hours, wherein the mixed acid solution is a solution obtained by mixing concentrated sulfuric acid and concentrated nitric acid;
[0018] Alternatively, the porous carbon electrode is calcined in air at 300-800° C. for 2-24 hours.
[0019] Preferably, the activation step comprises: soaking the pretreated porous carbon electrode in a palladium sulfate solution for 10-60 minutes.
[0020] The present invention provides an improved method for preparing the porous carbon electrode and its application in preparing a liquid flow battery;
[0021] The liquid flow battery includes any one of an all-vanadium liquid flow battery, an iron-chromium liquid flow battery, a polysulfide liquid flow battery, and a zinc-based liquid flow battery.
[0022] The advantages of the present application compared to the prior art are: an improved preparation method for porous carbon electrodes, which can uniformly load transition metals or transition metal sulfides on the surface of porous carbon electrodes through chemical plating and an optional sulfurization step after chemical plating. Therefore, through the above-mentioned improved preparation method of the present application, transition metals or transition metal sulfides as catalysts can be attached to the porous carbon electrodes of liquid flow batteries in large quantities and uniformly. After testing, the porous carbon electrodes after the improved treatment of the present application have the advantages of a wide area containing catalysts and high catalytic efficiency, which can effectively improve the kinetic performance of the active materials of liquid flow batteries and the battery power density, and provide a new method for the preparation of large-scale liquid flow battery electrode catalysts.
[0023] The improved preparation method of the porous carbon electrode or the porous carbon electrode provided by the present invention can be widely used in the preparation process of liquid flow batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a rate performance diagram of Experimental Example 1 of the present invention when the porous carbon electrode prepared in Example 1 is used as the negative electrode current collector.
[0025] Figure 2 This is a rate performance diagram of Experimental Example 1 of the present invention when the porous carbon electrode prepared in Example 2 is used as the negative electrode current collector.
[0026] Figure 3 This is a rate performance diagram of Experimental Example 2 of the present invention when the porous carbon electrode prepared in Example 3 is used as the negative electrode current collector.
[0027] Figure 4 This is a graph corresponding to the cycle performance when the porous carbon electrode prepared in Example 3 is used as the negative electrode current collector, provided in Experimental Example 2 of the present invention. DETAILED DESCRIPTION
[0028] In order to make the contents of the present application easier to understand, the technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application.
[0029] According to one aspect of the present invention, an improved method for preparing a porous carbon electrode comprises: performing chemical plating on the porous carbon electrode to plate a transition metal element onto the porous carbon electrode to obtain an improved porous carbon electrode;
[0030] Optionally, the improved preparation method further comprises the step of subjecting the transition metal element plated on the porous carbon electrode to a sulfurization treatment.
[0031] The improved preparation method of the porous carbon electrode provided by the present invention can make the transition metal or transition metal sulfide uniformly attached to the surface of the porous carbon electrode through chemical plating and an optional sulfurization step after chemical plating. Therefore, through the above-mentioned improved preparation method of the present application, the transition metal or transition metal sulfide used as a catalyst can be attached to the porous carbon electrode of the liquid flow battery in a large amount and uniformly. After testing, the porous carbon electrode after the improved treatment of the present application has the advantages of a wide area containing the catalyst and high catalytic efficiency, which can effectively improve the kinetic performance of the active material of the liquid flow battery and the battery power density, and provide a new method for the preparation of large-scale liquid flow battery electrode catalysts.
[0032] In a preferred embodiment of the present invention, the porous carbon electrode comprises one of carbon felt, graphite felt and carbon paper.
[0033] In a preferred embodiment of the present invention, the transition metal element includes at least one of Ni, Cu, Ag, Au, Zn, Cr, and Co.
[0034] As a preferred embodiment, the transition metal element loaded on the porous carbon electrode after chemical plating is one or more of Ni, Cu, Ag, Au, Zn, Cr, and Co metal elements, which can be recorded as Ni@C, Cu@C, Ag@C, Au@C, Zn@C, Cr@C, and Co@C.
[0035] In a preferred embodiment of the present invention, the temperature of the electroless plating solution is 20 to 95° C., and the electroless plating time is 5 to 30 minutes.
[0036] As a preferred embodiment, chemical plating is carried out within the above temperature range, which has a good chemical plating effect. Wherein: the plating solution temperature of chemical nickel plating is 75-95°C, and the plating solution temperature of chemical copper plating is 20-60°C. In the process of chemical nickel plating or copper plating, if the plating solution temperature of chemical plating is lower than the lower limit of the above temperature range, the rate of chemical plating will slow down; and if the plating solution temperature is higher than the upper limit of the above temperature range, it will affect the thickness of the chemical plating layer.
[0037] In a preferred embodiment of the present invention, the sulfiding liquid used in the sulfidation treatment is a polysulfide solution or a thioacetamide solution;
[0038] In a preferred embodiment, the polysulfide solution is preferably a Na 2S 2 solution;
[0039] Preferably, the concentration of the Na 2S 2 solution is 0.5 to 6 mol / L, preferably 1 mol / L;
[0040] Preferably, the concentration of the thioacetamide aqueous solution is 0.01-0.1 g / mL.
[0041] As a preferred embodiment, the transition metal sulfides loaded on the porous carbon electrode after sulfidation treatment are Ni XSY (x∈[1,3], y∈[1,4]), CuSX (x∈[0.5,1]), Ag2S, Au2S3, ZnS, CoXSY (x,y∈[1,4]), denoted as NiXSY@C, CuSX@C, Ag2S@C, Au2S3@C, ZnS@C, CoXSY@C.
[0042] In a preferred embodiment of the present invention, the reaction temperature of the sulfurization treatment is 80-200° C., and the reaction time of the sulfurization reaction is 2-10 h.
[0043] In a preferred embodiment of the present invention, before chemical plating, the steps of pre-treating and activating the porous carbon electrode are also included;
[0044] The pretreatment step includes: placing the porous carbon electrode in a mixed acid solution and heating it at 60-100° C. for 1-10 hours, wherein the mixed acid solution is a solution obtained by mixing concentrated sulfuric acid and concentrated nitric acid;
[0045] Alternatively, the porous carbon electrode is calcined in air at 300-800° C. for 2-24 hours.
[0046] As a preferred embodiment, the above-mentioned pretreatment step can effectively increase the hydrophilicity and electrical conductivity of the porous electrode.
[0047] In a preferred embodiment of the present invention, the activation step comprises: soaking the pretreated porous carbon electrode in a palladium sulfate solution for 10-60 minutes; preferably, the concentration of the palladium sulfate solution is 30-80 mg / L, and the solvent is 5% sulfuric acid.
[0048] According to one aspect of the present invention, a porous carbon electrode is provided. The porous carbon electrode is mainly prepared by the improved preparation method of the porous carbon electrode.
[0049] The porous carbon electrode provided by the present invention is mainly prepared by the improved preparation method of the porous carbon electrode. It can be seen from the improved method that a large amount of transition metals or transition metal sulfides are uniformly attached to the porous carbon electrode of the present invention, and the transition metals or transition metal sulfides are used as catalysts to effectively improve the active material dynamics of the liquid flow battery and increase the power density of the liquid flow battery.
[0050] According to one aspect of the present invention, an improved method for preparing the above-mentioned porous carbon electrode or the use of the above-mentioned porous carbon electrode in preparing a liquid flow battery.
[0051] The improved preparation method of the porous carbon electrode or the porous carbon electrode provided by the present invention can be widely used in the preparation process of liquid flow batteries.
[0052] Preferably, the flow battery includes any one of an all-vanadium flow battery, an iron-chromium flow battery, a polysulfide flow battery, and a zinc-based flow battery.
[0053] The technical solution of the present invention will be further described below in conjunction with embodiments.
[0054] Example 1
[0055] An improved method for preparing a porous carbon electrode, the method comprising:
[0056] 1. Pretreatment: Provide graphite felt as a porous carbon electrode, then place the porous carbon electrode in a mixed acid solution and heat it at 80°C for 5 hours to complete the pretreatment;
[0057] The mixed acid solution is a solution obtained by mixing concentrated sulfuric acid and concentrated nitric acid (concentrated sulfuric acid: concentrated nitric acid = 3:1).
[0058] 2. Activation: Soak the pretreated porous carbon electrode in a palladium sulfate solution for 20 minutes to complete the activation. The concentration of the palladium sulfate solution is 50 mg / L and the solvent is 5% sulfuric acid.
[0059] 3. Chemical plating: The activated porous carbon electrode is placed in a nickel-containing plating solution with a temperature of 85°C and a pH of 4.8. The nickel plating time is 11 minutes to obtain a porous carbon electrode uniformly loaded with Ni metal, which is recorded as Ni@GF.
[0060] Note: The above “GF” is the abbreviation of graphite felt.
[0061] The nickel plating solution composition is 25g / L NiSO4·7H20, 16g / L CH3COONa, 20g / L lactic acid, and 20g / L NaH2PO2.
[0062] Example 2
[0063] An improved method for preparing a porous carbon electrode, the method comprising:
[0064] 1. Pretreatment: same as in Example 1;
[0065] 2. Activation: same as Example 1;
[0066] 3. Chemical plating: same as in Example 1;
[0067] 4. Sulfidation treatment: The Ni@GF obtained in step 3 was placed in a 1M Na 2S 2 solution and subjected to a sulfidation treatment at 90°C for 10 h to obtain a porous carbon electrode uniformly loaded with transition metal nickel sulfide, denoted as Ni XSY@GF.
[0068] Test Example 1
[0069] In order to show that the porous carbon electrode after the improvement treatment of the present application can effectively improve the active material dynamics of the flow battery and increase the power density of the flow battery, the porous carbon electrodes prepared in the above Examples 1 and 2 are now subjected to rate performance testing, and the specific method is as follows:
[0070] 1. Preparation of liquid battery: The battery body includes a cation exchange membrane, a negative electrode and a positive electrode that divide the battery body into left and right chambers, wherein:
[0071] The positive electrode uses ordinary graphite felt, the positive electrode active material is 0.5M Na 4[Fe(CN)6] solution, and the negative electrode active material is 1M Na 2S2 solution;
[0072] The porous carbon electrode prepared in the above Examples 1 and 2 was used as a negative electrode in a polysulfide flow battery, and a polysulfide flow battery in which the negative electrode graphite felt was not loaded with any catalyst was tested as a comparison.
[0073] 2. Pump the positive and negative active materials into the positive and negative electrodes respectively, and charge and discharge the battery at constant current at different current densities.
[0074] After running for 2 cycles at 20mA cm-2, 40mA cm-2, 60mA cm-2, and 80mA cm-2, the polysulfide flow battery with no catalyst loaded on the negative electrode graphite felt could not be charged and discharged normally. However, when Ni metal and nickel sulfide were loaded on the negative electrode graphite felt, the battery could be charged and discharged normally and had relatively excellent catalytic performance.
[0075] The present invention plots the rate performance of the liquid batteries prepared in Examples 1 and 2.
[0076] Figure 1 This is a rate performance diagram of the porous carbon electrode prepared in Example 1 when used as the negative electrode current collector provided in this test example.
[0077] Figure 2 This is a rate performance diagram of the porous carbon electrode prepared in Example 2 when used as the negative electrode current collector provided in this test example.
[0078] Depend on Figure 1 , Figure 2It can be seen that nickel-plated graphite felt has an obvious catalytic effect on the conversion of substances in polysulfide solutions (without a catalyst, the battery cannot be charged and discharged normally). Figure 2 It represents the rate performance of the battery after a certain sulfurization of nickel-plated graphite felt. Compared with nickel-plated graphite felt, the battery performance is greatly improved, which shows that the catalytic effect of Ni XSY on polysulfides is better than that of metallic nickel.
[0079] Example 3
[0080] An improved method for preparing a porous carbon electrode, the method comprising:
[0081] 1. Pretreatment: same as in Example 1;
[0082] 2. Activation: same as Example 1;
[0083] 3. Chemical plating: The activated porous carbon electrode is placed in a nickel-containing plating solution with a temperature of 85°C and a pH of 4.8. The nickel plating time is 11 minutes to obtain a porous carbon electrode uniformly loaded with Ni metal, which is recorded as Ni@GF.
[0084] The nickel plating solution composition is 25g / L NiSO4·7H20, 16g / L CH3COONa, 20g / L lactic acid, and 20g / LNaH2PO2.
[0085] The above Ni@GF was placed in a copper plating solution at 50°C for chemical copper plating with a reaction time of 20 min to obtain a copper-plated porous carbon electrode, which was recorded as Cu@C.
[0086] The copper plating solution consists of 5 g / L CuCl 2, 30 g / L EDTANa 2, 10.5 g / L NaOH, and 10 mL / L 37% formaldehyde solution, with a pH of 12.6.
[0087] 4. Sulfidation treatment: The copper-plated porous carbon electrode obtained in step 3 is placed in a 1M Na2S2 solution for sulfidation at 90°C for 10 hours to obtain a porous carbon electrode uniformly loaded with transition metal copper sulfide, denoted as CuS X@C.
[0088] Test Example 2
[0089] In order to show that the porous carbon electrode after the improvement treatment of the present application can effectively improve the active material dynamics of the flow battery and increase the power density of the flow battery, the porous carbon electrode prepared in the above Example 3 is now subjected to rate performance testing, and the specific method is as follows:
[0090] 1. Preparation of liquid battery: The battery body includes a cation exchange membrane, a negative electrode and a positive electrode that divide the battery body into left and right chambers, wherein:
[0091] The positive electrode uses ordinary graphite felt, the positive electrode active material is 0.5M Na 4[Fe(CN)6] solution, and the negative electrode active material is 1M Na 2S2 solution;
[0092] The porous carbon electrode prepared in the above Example 3 is used as a negative electrode in a polysulfide flow battery.
[0093] 2. Pump the positive and negative active materials into the positive and negative electrodes respectively, and charge and discharge the battery at constant current at different current densities.
[0094] The battery was run for 2 cycles at 20mA cm-2, 40mA cm-2, 60mA cm-2, 80mA cm-2 and 100mA cm-2 respectively. By comparing Examples 1 to 3, it was found that the porous carbon electrode prepared in Example 3 had the best battery performance and better catalytic effect on polysulfides, so that higher current density can be achieved for charging and discharging, thereby greatly improving the power density of the liquid flow battery.
[0095] Figure 3 This is a rate performance diagram of the porous carbon electrode prepared in Example 3 when used as the negative electrode current collector provided in this test example.
[0096] Figure 4 This is a graph corresponding to the cycle performance when the porous carbon electrode prepared in Example 3 is used as the negative electrode current collector provided in this test example.
[0097] Depend on Figure 4 It can be seen that the use of sulfurized copper-coated graphite felt as the negative electrode of the flow battery for long-term cycling has the following results: Figure 4 As shown, the coulombic efficiency of the battery is stable at about 92%, and after multiple cycles of charge and discharge, the battery discharge capacity has basically no loss, indicating that the catalytic performance of the copper-plated graphite felt after sulfide is very stable.
[0098] The above embodiments are only used to illustrate the technical solutions of the embodiments of the present application, rather than to limit them. Although the embodiments of the present application are described in detail with reference to the above embodiments, it should be understood by those skilled in the art that the technical solutions described in the above embodiments can still be modified, or some of the technical features can be replaced by equivalents, without departing from the spirit and scope defined by the claims of the present application.
Claims
1. An improved method for preparing a porous carbon electrode, characterized in that: The method comprises: Chemical plating is performed on the porous carbon electrode to plate the transition metal element on the porous carbon electrode to obtain an improved porous carbon electrode; Optionally, the improved preparation method further comprises the step of subjecting the transition metal element plated on the porous carbon electrode to a sulfurization treatment.
2. The improved method for preparing a porous carbon electrode according to claim 1, characterized in that: The porous carbon electrode comprises one of carbon felt, graphite felt and carbon paper.
3. The improved method for preparing a porous carbon electrode according to claim 1, characterized in that: The transition metal element includes at least one of Ni, Cu, Ag, Au, Zn, Cr, and Co.
4. The improved method for preparing a porous carbon electrode according to claim 1, characterized in that: The plating solution temperature of the chemical plating is 20-95° C., and the time of the chemical plating is 5-30 minutes.
5. The improved method for preparing a porous carbon electrode according to claim 1, characterized in that: The sulfiding liquid used in the sulfiding treatment is a polysulfide solution or a thioacetamide solution, and the polysulfide solution is preferably a Na 2S 2 solution.
6. The improved method for preparing a porous carbon electrode according to claim 5, characterized in that: The reaction temperature of the sulfurization treatment is 80-200° C., and the reaction time of the sulfurization reaction is 2-10 hours.
7. The improved method for preparing a porous carbon electrode according to claim 1, characterized in that: Before the chemical plating, the porous carbon electrode is also pretreated and activated in sequence; Wherein, the pre-processing step includes: The porous carbon electrode is placed in a mixed acid solution and heated at 60 to 100° C. for 1 to 10 hours, wherein the mixed acid solution is a solution obtained by mixing concentrated sulfuric acid and concentrated nitric acid; Alternatively, the porous carbon electrode is calcined in air at 300-800° C. for 2-24 hours.
8. The improved method for preparing a porous carbon electrode according to claim 7, characterized in that: The activation step comprises: The pretreated porous carbon electrode is immersed in a palladium sulfate solution for 10-60 minutes; Preferably, the concentration of the palladium sulfate solution is 30-80 mg / L, and the solvent is 5% sulfuric acid.
9. Use of the improved preparation method of the porous carbon electrode according to any one of claims 1 to 8 in the preparation of a liquid flow battery; The liquid flow battery includes any one of an all-vanadium liquid flow battery, an iron-chromium liquid flow battery, a polysulfide liquid flow battery, and a zinc-based liquid flow battery.